Gender gaps in Spain: Policies and outcomes over the last three decades - Nezih Guner; Ezgi Kaya; Virginia Sánchez Marcos (SERIEs - Journal of the Spanish Economic Association, 2014)
We document recent trends in gender equality in employment and wages in Spain. Despite an impressive decline in the gender gap in employment, females are still less likely to work than males: about 76 % of working age males and 63 % of working age females were employed in 2010. If females work they are more likely to be employed part time and with temporary contracts. The large increase in female employment, from 28 % in 1977 to 63 % in 2010, was accompanied by a significant decline in fertility. The gender gap in wages, after controlling for worker and job characteristics as well as for selection, is high. It was about 20 % in 2010, quite close to its value in 1994. Furthermore, the gender gap in wages is driven mainly by differences in returns to individual characteristics. While women are more qualified than men in observable labor market characteristics, they end up earning less. There have been several important policy changes that try to help families reconcile family responsibilities with market work. The existing literature suggests that households do react to incentives generated by different policies and policy changes are at least partly responsible for changes in female labor supply. In recent decades, the large inflow of immigrants, who provided relatively cheap household services, allowed more educated women to enter the labor market. Policy challenges, however, remain.
Keywords: J16; J21; J22; J24; 330; Gender employment gap; Gender wage gap; Occupational segregation; Quantile regressions; Selection; Public policy